Development and evaluation of antimicrobial herbal formulations containing the methanolic extract of Samadera indica for skin diseases - Vidya Viswanad; N A Aleykutty; B Jayakar; Subin Mary Zacharia; Litha Thomas (Wolters Kluwer Medknow Publications, 2012)
Samadera indica Gaetrn (Simaroubaceae) is claimed to possess various pharmacological activities like antioxidant, antifungal, antitumor, antiviral, and so on, but its taste is bitter. The aim of the present study is to investigate the toxicity of the methanolic extract and to develop suitable herbal formulations of the methanolic extract of Samadera indica, having efficient antimicrobial activity. The methanolic extract prepared from the dried leaves of Samadera indica by continuous hot percolation, were used to examine the toxicity, according to the OECD 423 guidelines, in Swiss Albino mice. Topical formulations were prepared by incorporating Samadera indica (5% w / w) in an emulsifying ointment and a carbopol gel base and evaluated for physical parameters and in-vitro antimicrobial activity (S. aureus, P. aeruginosa and C. albicans). The study reveals that no animals under the study showed any clinical signs of toxicity or mortality when administered a dose of 5 - 2000 mg / kg body weight. Therefore, the maximum tolerated dose of the methanolic extract of Samadera indica was above 2000 mg / kg body weight. The formulated ointment and gel had acceptable physical parameters that showed that they were compatible with the skin, and in addition to this, these formulations passed the short-term stability studies. The in-vitro antimicrobial activity studies showed that the formulated ointment showed significantly strong (p < 0.05) activity against S. aureus, P. aeruginosa and C. albicans than the formulated gel. Thus, the present study concludes that the formulated ointment and gel are safe and efficient antimicrobial formulations for the topical delivery of the methanolic extract of Samadera indica.